A preliminary survey of medium and large‐sized mammals from Lebu Natural Protected Forest, Southwest Showa, Ethiopia. Issue 21 (22nd October 2019) - Qufa, Chala Adugna; Bekele, Afework
Abstract: This study was conducted to determine the species composition and diversity of medium and large‐sized mammals from Lebu Natural Protected Forest, Ethiopia. Surveys were conducted to record mammals through direct observation and indirect evidence from three habitat types, namely: natural forest, bushland, and riverine forest. A total of 15 mammalian species were recorded. The species recorded were Papio anubis, Chlorocebus aethiops, Tragelaphus scriptus, Canis aureus, Crocuta crocuta, Panthera pardus, Procavia capensis, Colobus guereza, Sylvicapra grimmia, Orycteropus afer, Helogale parvula, Hystrix cristata, Lepus fagani, Potamochoerus larvatus, and Phacochoeus africanus . A total of 223 records of observations were compiled. About 74% of these records ( N  = 167) were obtained from direct sight, whereas the rest was recorded through indirect evidence. The dominant order recorded was order Primates (57.4%) followed by order Artiodactyla (17.5%) while the least record was order Lagomorpha (1.34%). The species richness varied across the stratified habitat types. However, there is no significant difference in Shannon–Wiener Index values between the habitat types. The species diversity of the study area was H ′ = 2.119. The present study area is of great potential area for the conservation of the species. Long‐term detailed studies should be carried out for effective conservation and management initiatives in the study area. Abstract : Medium‐ and large‐sized mammals from Lebu Natural Protected Forest of Ethiopia were surveyed. The area will contribute to the conservation of the mammal species. Long‐term detailed studies should be carried out for effective conservation and management initiative in the study area.